COVID-19: Mental Health and Academic Performance Among University Students - Ross Azura, Zahit; Sheilla Lim, Omar Lim; Joanne Yi Ling, Li (UNIMAS Publisher, 2022)
Different personality and mental health status may contribute differently to academic outcome. Hence, the main motivation of this study is to access the association of personality and mental health on academic performances in distance learning. This research applied a quantitative research method, using survey-based questionnaires, namely Ten Item Personality Inventory (TIPI) for personality traits and 12-Item General Health Questionnaire (GHQ-12) for mental health status. A total of 140 Undergraduates from all faculties in University Malaysia Sarawak (UNIMAS) were picked and demographic profile was analysed through the descriptive and correlational analysis using both Pearson and Spearman correlation tests. The results showed a significant relationship between mental health and the Undergraduate students’ academic performance in GPA. Specifically, the loss of confidence factor was the only mental health factor that demonstrated a significantly negative, but weak correlation with their GPA. The rest of the hypotheses were dismissed. Hence, according to the findings from this research, it can be concluded that the higher the score for mental health status, the higher the tendency for the students to experience negative mental illness. Consequently, affecting their academic performances.